REPRODUCTIVE FACTORS AND COLORECTAL CANCER RISK. Case - control study. - Adriana Ruseva; Radka Lazarova; Ilko Kosturkov; Vesselina Ianachkova; Stella Yordanova; Zhivka Boneva; Diana Nikolovska (Peytchinski Publishing, 2015)
Colorectal cancer is one of the most common cancers worldwide. The role of the female sex hormones in the etiology of the disease is very intriguing. Reproductive factors are surrogate measure of lifetime exposition to the sex hormones. Purpose: Our aim is to investigate the association between the reproductive factors and colorectal carcinoma risk. Materials and methods: We include 234 Bulgarian women in our study - 117 cases with colorectal cancer and the same number of healthy controls. Cases are divided into three groups according to the localization of the tumor. We conduct case-control study, using questionnaires about reproductive factors. We use the following statistical methods - descriptive, variational analysis, binary logistic regression. Results: We observed that only the age at menopause is associated with colorectal cancer risk, and this factor has strongest protective effect in the proximal colon (95% CI - 0,051-0,781, OR - 0,200, p - 0,021). Conclusion: Analyzing our data we observed that among Bulgarian women the only reproductive factor that show association with the risk of colorectal cancer is the age at menopause.